For the Unification of Italy from the South. The political experience of Giacinto Albini (Il Risorgimento. Rivista di storia moderna e contemporanea, 2024)
Drawing from the most recent historiographical acquisitions regarding the path to Italian Unification from the South, this essay specifically analyzes the forms and methods of construction and action of Southern patriotic networks between 1857 and 1861. Within this framework, from the failed Pisacane expedition to the Lucanian uprising of August 18, 1860, the reconstruction of the life trajectory of the Lucanian Giacinto Albini highlights not only the decisive and original contribution to the unification cause of the southern provinces but also the gradual marginalization, following the proclamation of a united Italy, of many of those protagonists who, while actively participating in the challenging Risorgimento journey, were deemed incompatible with the institutions of the new State under construction.
Keywords: Italian Unification; Expedition of Pisacane; Lucanian uprising; Southern Italy; Basilicata; Giacinto Albini